2017
DOI: 10.1073/pnas.1620626114
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into caspase-9 activation by the structure of the apoptosome holoenzyme

Abstract: Mammalian intrinsic apoptosis requires activation of the initiator caspase-9, which then cleaves and activates the effector caspases to execute cell killing. The heptameric Apaf-1 apoptosome is indispensable for caspase-9 activation by together forming a holoenzyme. The molecular mechanism of caspase-9 activation remains largely enigmatic. Here, we report the cryoelectron microscopy (cryo-EM) structure of an apoptotic holoenzyme and structureguided biochemical analyses. The caspase recruitment domains (CARDs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 33 publications
8
109
0
2
Order By: Relevance
“…We also estimated the k cat /K M of ΔCARD-His 6 against procaspase-3, and observed a similar decrease in catalytic efficiency than that of WT (Figures 2E–2G). While other studies have reported ΔCARD being more active than full-length cleaved caspase-9 (1113), we consistently and reproducibly observed the opposite. Both the ΔCARD caspase-9 which was allowed to autoprocess at the intersubunit linker (ΔCARD-His 6 in Figure 2A) and ΔCARD caspase-9 refolded from separately expressed large and small subunits (ΔCARD in Figure 2A) were less active than full-length cleaved caspase-9.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…We also estimated the k cat /K M of ΔCARD-His 6 against procaspase-3, and observed a similar decrease in catalytic efficiency than that of WT (Figures 2E–2G). While other studies have reported ΔCARD being more active than full-length cleaved caspase-9 (1113), we consistently and reproducibly observed the opposite. Both the ΔCARD caspase-9 which was allowed to autoprocess at the intersubunit linker (ΔCARD-His 6 in Figure 2A) and ΔCARD caspase-9 refolded from separately expressed large and small subunits (ΔCARD in Figure 2A) were less active than full-length cleaved caspase-9.…”
Section: Resultssupporting
confidence: 69%
“…Prior to our work there has been no data to suggest that there are existing interactions between the CARD and the catalytic core of caspase-9. However, there have been reports that point to an inhibitory role of CARD in caspase-9 activity prior to apoptosome binding, either by potentially interfering with caspase-9 homodimerization (11), or by binding to the active site and/or other regions of caspase-9 (13) to keep the enzyme in its latent state, and that Apaf-1 CARD binding relieves this inhibition. Here we observed that the CARD directly participates in stabilizing interactions with the core of caspase-9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged or persistent PTP opening causes mitochondrial depolarization and release of cytochrome c from the mitochondrial intermembrane space. Cytochome c is required for the activation of the initiator of apoptosis, caspase-9, by forming the apoptosomic complex with Apaf-1 (Li et al 2017). Such complex activates the effector caspase-3 and triggers a feedback loop for mitochondrial disruption through cleavage of anti-apoptotic Bcl-2 family proteins (Chen et al 2007).…”
Section: Mitochondrial-dependent Apoptosis and Ca2+ Dysregulationmentioning
confidence: 99%
“…Almost concurrently, the Akey (Cheng et al, 2016) and Shi (Li et al, 2017) groups reported two independently determined cryo-EM structures of the CARD disk in the context of the holo-apoptosome (Figure 1C), which were refined without imposing the seven-fold symmetry and reached sufficient resolution to visualize α helices in the CARDs.…”
mentioning
confidence: 99%